HUBUNGAN ANTARA SISWA MENGIKUTI ORGANISASI SISWA INTRA SEKOLAH DAN KEDISIPLINAN BELAJAR DENGAN PRESTASI BELAJAR SOSIOLOGI SISWA KELAS X SMA NEGERI 6 SURAKARTA TAHUN PELAJARAN 2012/2013 - Ihsani, Fauzan (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
ABSTRACTThis research has purpose to know: (1) relation of being active OSISOrganization with students sociologi learning achivement (2) relation of studentslearning discipline with students learning achievement (3) Relation of being activeOSIS organization and students learning discipline with learning achievementstudents class X SMA NEGERI 6 SURAKARTA.Method that used in this research is correlation descriptive. Researchpopulation is students class X SMA NEGERI 6 SURAKARTA learning years2012/2013, total 70 students. Sample takes with random sampling technique total20 students. Data takes technique do with questioner technique and grade schoolledger sociology lesson achievement. Statistic analysis technique folds correlationcoefficient analysis.Based from research output can take conclusion: (1) hypothesis 1 ?thereis correlation that significant enough between being active OSIS Organizationwith students learning achivement students class X SMA NEGERI 6SURAKARTA SURAKARTA learning years 2012/2013?. This case can see fromanalysis data output that showing r 1y = 0,166 and sig = 0, 08. (2) Hypothesis 2?there is correlation that significant between students learning discipline withstudents learning achivement students class X SMA NEGERI 6 SURAKARTASURAKARTA learning years 2012/2013?. This case can see from analysis dataoutput that showing r 2y = 0,193 and sig = 0, 05. (3) Hypothesis 3 ?there is foldcorrelation that significant less between of being active OSIS organization andstudents learning discipline with learning achievement students class X SMANEGERI 6 SURAKARTA learning years 2012/2013?. This case can see fromanalysis data output that showing Ry ( 1 2) = 0,214 and sig = 0, 21.Keyword: being active in organization, discipline learning, and learningachievement